2020
DOI: 10.3390/ijerph17103593
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Polish Version of Task and Ego Orientation in Sport Questionnaire (TEOSQ)

Abstract: The main aim of the study was to assess the psychometric properties of the Polish version of the task and ego orientation in sport questionnaire (TEOSQ). The study covered 651 athletes aged 19.2 years, SD (Standard deviation) = 2.21. The task and ego orientation in sport questionnaire (TEOSQ) and sport motivation scale (SMS-28) were used. Cronbach’s Alpha for the ego subscale was 0.84, and for the task subscale 0.81 (McDonald’s omega was 0.84, 0.82 respectively). The reliability of the test-retest with two wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 28 publications
(40 reference statements)
2
29
0
Order By: Relevance
“…The model presented by authors also obtained not ideal but acceptable fit indices (TLI = 0.90, root mean square = 0.09) [4]. The obtained values indicated that the POSQ questionnaire model was better suited to the data than the model (the first unadjusted model) of the Polish version of the TEOSQ questionnaire presented by the authors in the earlier publication [5]. However, this issue should be treated very carefully because it requires further analysis of the same data samples.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…The model presented by authors also obtained not ideal but acceptable fit indices (TLI = 0.90, root mean square = 0.09) [4]. The obtained values indicated that the POSQ questionnaire model was better suited to the data than the model (the first unadjusted model) of the Polish version of the TEOSQ questionnaire presented by the authors in the earlier publication [5]. However, this issue should be treated very carefully because it requires further analysis of the same data samples.…”
Section: Discussionmentioning
confidence: 83%
“…These aspects may indicate a moderating role of both tools (POSQ, TEOSQ) [17]. The relationships between the task orientation measured by the TEOSQ questionnaire and the intrinsic motivation components (SMS-28) presented in the publication which concerned the Polish version of the TEOSQ questionnaire were more than twice as high [5]. On the other hand, the relationship between the POSQ task orientation and intrinsic motivation was not always clear.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations